The Faceless Face: The Paradox of Bureaucratic Digitization in Indonesia: Wajah Tanpa Nama: Paradoks Digitalisasi Birokrasi di Indonesia - Efendy, Chelsea Shine; Santoso, Cornelia Editha; Thiolla, Victoria Gledie; Josephine, Anastasia Mandy (Academia Open, 2026)
General Background The digitization of bureaucracy in Indonesia is promoted to improve efficiency, transparency, and integration in public administration. Specific Background In practice, digital systems increasingly determine administrative recognition, as illustrated by the absence of valid mining permits in national databases despite their continued legal validity. Knowledge Gap Existing discussions have insufficiently addressed how digitalization reshapes the conceptual foundation of administrative law, particularly the notion of Administrative Decisions (KTUN) and the locus of accountability. Aims This study analyzes the implications of administrative depersonalization on the concept of KTUN, judicial review in administrative courts, and the protection of citizens’ rights. Results The findings reveal a paradox in which reliance on automated systems produces administrative deadlock, dualism between normative legality and digital administrative validity, and ambiguity in determining accountable actors. The study also identifies difficulties in defining dispute objects and tracing decision-making processes in system-generated outputs. Novelty This research offers a conceptual reconstruction of administrative law by situating digital systems as instruments rather than substitutes for legal subjects, emphasizing the continued centrality of human discretion and responsibility. Implications The study underscores the necessity of integrating digital governance within constitutional principles, ensuring that efficiency-driven systems do not undermine legal certainty, justice, and human dignity in administrative practices. Highlights: Automated administrative systems generate dual validity between legal recognition and database status. Judicial examination becomes complex due to system-based outputs lacking clear decision-makers. Human discretion remains essential to maintain accountability and protect citizens’ rights. Keywords: Digital Bureaucracy, Administrative Depersonalization, Administrative Decisions, E-Government, Legal Accountability